The Genomic Signature and Transcriptional Response of Metal Tolerance in Brown Trout Inhabiting Metal‐Polluted Rivers - Josephine R. Paris; R. Andrew King; Joan Ferrer Obiol; Sophie Shaw; Anke Lange; Vincent Bourret; Patrick B. Hamilton; Darren Rowe; Lauren V. Laing; Audrey Farbos; Karen Moore; Mauricio A. Urbina; et al. (Molecular Ecology, 2025)
Industrial pollution is a major driver of ecosystem degradation, but it can also act as a driver of contemporary evolution. As a result of intense mining activity during the Industrial Revolution, several rivers across the southwest of England are polluted with high concentrations of metals. Despite the documented negative impacts of ongoing metal pollution, brown trout ( Salmo trutta L.) survive and thrive in many of these metal‐impacted rivers. We used population genomics, transcriptomics, and metal burdens to investigate the genomic and transcriptomic signatures of potential metal tolerance. RADseq analysis of six populations (originating from three metal‐impacted and three control rivers) revealed strong genetic substructuring between impacted and control populations. We identified selection signatures at 122 loci, including genes related to metal homeostasis and oxidative stress. Trout sampled from metal‐impacted rivers exhibited significantly higher tissue concentrations of cadmium, copper, nickel and zinc, which remained elevated after 11 days in metal‐free water. After depuration, we used RNAseq to quantify gene expression differences between metal‐impacted and control trout, identifying 2042 differentially expressed genes (DEGs) in the gill, and 311 DEGs in the liver. Transcriptomic signatures in the gill were enriched for genes involved in ion transport processes, metal homeostasis, oxidative stress, hypoxia, and response to xenobiotics. Our findings reveal shared genomic and transcriptomic pathways involved in detoxification, oxidative stress responses and ion regulation. Overall, our results demonstrate the diverse effects of metal pollution in shaping both neutral and adaptive genetic variation, whilst also highlighting the potential role of constitutive gene expression in promoting metal tolerance.

Experimental evidence indicates that native freshwater fish outperform introduced Gambusia in mosquito suppression when water temperature is below 25°C - Craig Lawrence; Neil Rutherford; Rod Hamilton; Dean Meredith (Hydrobiologia, 2016)

Morphological characterization of seeds of three Australian wild Citrus species (Rutaceae): Citrus australasica F. Muell., C. inodora F.M. Bailey and C. garrawayi F.M. Bailey - Kim N. Hamilton; Sarah E. Ashmore; Rod A. Drew (Genetic Resources and Crop Evolution, 2008)